Long-term outcomes in patients newly diagnosed with iron deficiency anaemia in general practice: a retrospective cohort study - Schop, Annemarie (BMJ Open, 2019)
OBJECTIVES: To describe all iron deficiency anaemia (IDA)–related causes during follow-up of patients newly diagnosed with IDA and to assess whether a delayed colorectal cancer (CRC) diagnosis influences survival. DESIGN AND SETTING: Retrospective cohort study of patients from general practices in the Dordrecht area, the Netherlands. PARTICIPANTS: Men and women aged ≥50 years with a new diagnosis of IDA (ie, no anaemia 2 years previously). METHOD: From February 2007 to February 2018, all relevant data were collected from the files of the referral hospital. Early IDA-related cause was defined as established within 18 weeks after IDA diagnosis. Cox proportional-hazards regression was used to analyse survival of patients with CRC diagnosis. RESULTS: 587 patients with IDA were included with a median follow-up of 4.6 years. Early and late IDA-related causes could be established in 32% and 8% of patients, respectively. Early and late CRC was found in 8% and 2% of patients, respectively, and were located mainly right sided. After adjustment for age, gender and TNM classification, mortality risk was lower in patients with IDA with early CRC diagnosis, but not significantly (HR 0.30, 95% CI 0.09 to 1.02). CONCLUSION: Even with extended follow-up, the cause of IDA remains elusive in the majority of patients with IDA in general practice. However, patients with IDA are at increased risk for in particular right-sided CRC and a late diagnosis of CRC appears to have a detrimental effect on survival in patients with IDA.